Benchmarking critical success factors perceptions and practices in Malaysian automotives manufacturing companies - Baba Md Deros,; Sha'ri Mohd Yusof,; Azhari Md Salleh, (2007)
This article is based on a survey conducted on the top management’s perceptions and practices of critical success factors (CSFs) with respect to benchmarking implementation in Malaysian automotive components manufacturing companies. The main objective of this paper is to provide empirical evidence on top management’s practices of CSFs for implementing benchmarking among eight different companies categories, comprising of all respondents; quality certiﬁed; non-quality certiﬁed; Small and Medium Enterprise (SME); large; 100% locally owned; 100% foreign owned; and joint venture companies. To achieve this objective, the authors developed a questionnaire comprising of nine major CSFs and 49 elements, checked for reliability and validity by experts and practitioners. The analyses from 68 respondent companies showed the CSFs for benchmarking implementation were practiced at low to moderate level. On overall, there is a signiﬁcant difference between the CSFs perceived level of importance and extent of practice by the respondent companies. Pair samples t-test results showed there is a signiﬁcant difference between the level of importance and practices in all CSFs in quality certiﬁed, large, SME, 100% local and joint venture companies. The survey results also showed no signiﬁcant difference in terms of level of importance and practice of all the CSFs in 100% foreign companies. In non-quality certiﬁed companies there is no signiﬁcant difference in terms of level of importance and practice except for four CSFs. Finally, the paper concludes with some suggestions on the steps on how to improve the CSFs adoption rate and thus enhanced business competitiveness and excellence in Malaysian automotive manufacturing companies